DOMESTIC AND NATIONAL: THE PROBLEM OF CHOOSING “BETWEEN TWO FORCES” (ON THE MATERIAL OF PLAYS BY LIUDMYLA STARYTSKA-CHERNIAKHIVSKA AND VOLODYMYR VYNNYCHENCO) - Процюк, Л. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analises the drama works «Last Sheaf» by Liudmyla Starytska-Cherniakhivska and «Between Two Forces» by Volodymyr Vynnychenko in aspects of the choice of the domestic and national existence problems. The author analyses conflict, images of the work, the plot, composition and other aspects of poetics. The article proofs psychologism as a main feature of the Ukrainian drama at the beginning of last century.